Prevalence and Natural Course of Transverse Ligament of the Atlas Calcification in Asymptomatic Healthy Individuals. Issue 24 (15th December 2018) - Anno, Masato; Oshima, Yasushi; Taniguchi, Yuki; Matsubayashi, Yoshitaka; Kato, So; Soma, Kazuhito; Oka, Hiroyuki; Hayashi, Naoto; Tanaka, Sakae
Abstract : Study Design: A retrospective cross-sectional study. Objective: The aim of this study was to assess the prevalence and natural course of calcification of the transverse ligament of the atlas (TLA) in healthy subjects and to investigate the relationship between the calcified lesion and clinical factors. Summary of Background Data: The prevalence and etiology of TLA calcification in healthy individuals remain uncertain. Methods: We enrolled 1136 participants undergoing computed tomography (CT) scans in their routine medical checkups. The calcified lesion of the TLA was classified into two types: type 1, thin calcifications (<2 mm) and type 2, curvilinear lesions (>2 mm). We evaluated the natural course of the lesion and compared each clinical variable among subjects with and without TLA calcifications after adjusting for age and sex using propensity score matching techniques. Results: TLA calcification was present in 40 participants (3.5%; 31 males and 9 females; mean age, 65.3 years), and the frequency increased with age ( P = 0.001). Both types 1 and 2 calcifications were observed in 26 (65%) and 14 cases (35%), with mean ages of 63.0 and 69.4 years ( P = 0.033), respectively. Of these, 37 (93%) underwent another medical checkup afterward, and the morphological changes were further assessed. Five cases (14%) showed enlargement [one case (4%) in type 1 vs . four cases (33%) in type 2], whereas six cases (16%) had disappearance or decrease [six cases (24%) in type 1 vs . 0 cases in type 2, which was statistically significant ( P = 0.019)]. A one-to-one propensity score matching analysis revealed no significant differences in clinical variables among subjects with and without TLA calcifications. Conclusion: The prevalence of the TLA calcification was not rare in normal subjects. Our results suggest that the calcified lesion could be morphologically changed on a yearly basis and may be associated with the normal aging process. Level of Evidence: 3